The link between agricultural trade, climate change and food security Tariff elimination for environmentally efficient agricultural goods (EEAG) - Papendieck, Sabine; Idigoras, Gustavo (2017)
International agricultural trade must positively redistribute food production, increasing both: quantity and quality in all regions, and consequently ensuring food security level on a global scale. On the other hand, the world has entered a new era of action for sustainable development. As human life depends on land and water for sustenance and survival, the process of climate change and the multilateral commitments consequently assumed by the international agreement have imposed on agricultural production a new context: environmental efficiency.